Decreased facial expression variability in patients with serious cardiopulmonary disease in the emergency care setting. Issue 1 (14th July 2014) - Kline, Jeffrey A; Neumann, Dawn; Haug, Melissa A; Kammer, David J; Krabill, Virginia A
Abstract : Background and objective: The hypothesis of the present work derives from clinical experience that suggests that patients who are more ill have less facial expression variability in response to emotional cues. Methods: Prospective study of diagnostic accuracy from a convenience sample of adult patients with dyspnoea and chest pain in an emergency department. Patients viewed three stimulus slides on a laptop computer that were intended to evoke a change in facial affect. The computer simultaneously video recorded patients' facial expressions. Videos were examined by two independent blinded observers who analysed patients' facial expressions using the Facial Action Coding System (FACS). Patients were followed for predefined serious cardiopulmonary diagnosis (Disease+) within 14 days (acute coronary syndrome, pulmonary embolism, pneumonia, aortic or oesophageal disasters or new cancer). The main analysis compared total FACS scores, and action units of smile, surprise and frown between Disease+ and Disease−. Results: Of 50 patients, 8 (16%) were Disease+. The two observers had 92% exact agreement on the FACS score from the first stimulus slide. During stimulus slide 1, the median of all FACS values from Disease+ patients was 3.4 (1st–3rd quartiles 1–6), significantly less than the median of 7 (3–14) from D−patients (p=0.019, Mann–Whitney U). Expression of surprise had the largest difference between Disease+ and Disease−(area under the receiver operating characteristic curve 0.75, 95% CI 0.52 to 0.87). Conclusions: With a single visual stimulus, patients with serious cardiopulmonary diseases lacked facial expression variability and surprise affect. Our preliminary findings suggest that stimulus-evoked facial expressions from emergency department patients with cardiopulmonary symptoms might be a useful component of gestalt pretest probability assessment.